Spectrum of ascending aortic aneurysms at a peri-urban tertiary hospital: an echocardiography-based study - Meel, Ruchika; Hasenkam, Michael; Goncalves, Ricardo; Blair, Kelly; Mogaladi, Shungu (Frontiers in Cardiovascular Medicine, 2023)
Introduction Thoracic ascending aortic (TAA) aneurysms are an important cause of disability and death and require early detection for effective management. Currently, there is a paucity of data from Africa pertaining to TAA aneurysms. This study describes the spectrum of TAA aneurysms at a peri-urban tertiary hospital. Methods A descriptive retrospective study based on clinical and echocardiographic imaging data of patients with TAA aneurysms from October 2017–October 2022. Advanced strain imaging was performed to measure left ventricular (LV) basal, apical, and global longitudinal strain as well as circumferential strain (CS) of the ascending aorta as a proxy measurement of aortic compliance. Results The study comprised 139 cases of TAA aneurysms (52.5% females) with a mean age of 50 ± 14.8 years with 45 age and gender matched controls. Most cases (95%) were of African ethnicity. The main etiologies were hypertension (41.7%), HIV (36.6%), connective tissue disease (10.7%), congenital (2.2%) and mixed pathologies (8.6%). Two-thirds of patients (69.7%) presented in heart failure, 10% presented with aortic dissection. Thirty percent of the patients were classified as New York Heart Association (NYHA) class I, 59.7% NYHA II, 8.6% NYHA III and two patients NYHA class IV. Echocardiography revealed enlarged aortic dimensions compared to controls (P < 0.001). TAA aneurysms were complicated by severe aortic regurgitation (AR) in half (50.3%) of patients, moderate AR in 25.8%, and mild AR in 14.3%. The mean LV ejection fraction (46.9 ± 12.7%) was reduced compared to controls (P < 0.001). Aortic CS was reduced compared to controls [4.4 (3.2–6.2) % vs. 9.0 (7.1–13.4) %, P < 0.001]. Aortic stiffness was higher in the aortic aneurysm group compared to controls (15.39 ± 20.65 vs. 5.04 ± 2.09, P = 0.001). LV longitudinal strain (−13.9 ± 3.9% vs. 18.1 ± 6.7%), basal CS (−13.9 ± 5.6% vs. −17.9 ± 5.8%) and apical CS (−8.7 ± 8.5% vs. −30.6 ± 3.8%) were reduced compared to controls (P < 0.001). Most patients were on diuretic and anti-remodeling therapy. Surgery was performed in 29.4% and overall mortality was 7.9%. Mortality for acute aortic dissection was 40%. Conclusion TAA aneurysms associated with hypertension and HIV are common in this predominantly African female population and are associated with considerable morbidity and mortality. Two-dimensional echocardiography and advanced strain imaging are potential tools for detecting and risk stratifying TAA aneurysms.